Quantitative polarization‑sensitive super‑resolution solid immersion microscopy reveals biological tissues’ birefringence in the terahertz range - Chernomyrdin, Nikita V.; Ilenkova, D. R.; Zhelnov, V. A.; Alekseeva, Anna I.; Gavdush, Arsenii A.; Musina, Guzel R.; Nikitin, Pavel V.; Kucheryavenko, Anna S.; Dolganova, Irina N.; Spektor, Igor E; Tuchin, Valery V.; Zaytsev, Kirill I. (Scientific Reports [Еlectronic resource])
Terahertz (THz) technology offers a variety of applications in label-free medical diagnosis and therapy, majority of which rely on the effective medium theory that assumes biological tissues to be optically isotropic and homogeneous at the scale posed by the THz wavelengths. Meanwhile, most recent research discovered mesoscale ( ) heterogeneities of tissues; is a wavelength. This posed a problem of studying the related scattering and polarization effects of THz-wave–tissue interactions, while there is still a lack of appropriate tools and instruments for such studies. To address this challenge, in this paper, quantitative polarization-sensitive reflection-mode THz solid immersion (SI) microscope is developed, that comprises a silicon hemisphere-based SI lens, metal-wire-grid polarizer and analyzer, a continuous-wave 0.6 THz ( = 500 μm) backward-wave oscillator (BWO), and a Golay detector. It makes possible the study of local polarization-dependent THz response of mesoscale tissue elements with the resolution as high as 0.15 . It is applied to retrieve the refractive index distributions over the freshly-excised rat brain for the two orthogonal linear polarizations of the THz beam, aimed at uncovering the THz birefringence (structural optical anisotropy) of tissues. The most pronounced birefringence is observed for the Corpus callosum, formed by well-oriented and densely-packed axons bridging the cerebral hemispheres. The observed results are verified by the THz pulsed spectroscopy of the porcine brain, which confirms higher refractive index of the Corpus callosum when the THz beam is polarized along axons. Our findings highlight a potential of the quantitative polarization THz microscopy in biophotonics and medical imaging.